Job burnout prediction in two Colombian companies using communication patterns via email (2019)
The syndrome of job burnout is a response to the prolonged exposition to chronic stress at work. It can result in health problems, accidents at work, and, in some cases, in the suicide of the person who is suffering it. Most people discover that they have burnout when it is too late, and they need to stop working. The main objective of this investigation is to give an early identification of burnout syndrome when there is still scope to change working conditions. We present in this document a machine learning-based tool that provides an early warning about a worker's potential risk of suffering from burnout symptoms in real-time. In this study, we constructed a methodology and software for predicting job burnout based on communication patterns via email in two Colombian companies.